Analisis Kinerja Jaringan Distribusi LPG: Studi Kasus di Kecamatan Compreng - Sunardhi, Yoseph; Ikar, Arief; Lamhot, Nesta; Safira, Lintang (Universitas Pahlawan Tuanku Tambusai, 2025)
LPG distribution in Compreng Subdistrict faces challenges in terms of inadequate road infrastructure and fluctuating demand. This study aims to analyze the performance of the LPG distribution network using the Vehicle Routing Problem (VRP) method to optimize distribution routes. Primary data were collected through observation and interviews, then processed using VRP to produce optimal routes considering vehicle capacity and customer demand. The results showed that optimal distribution routes could reduce travel distance and operational costs, thus improving the efficiency of LPG distribution.